Heterologous Hyaluronic Acid Production in Kluyveromyces lactis - V. Gomes, Antonio M. (Microorganisms, 2019)
Hyaluronic Acid (HA) is a biopolymer composed by the monomers Glucuronic Acid (GlcUA) and N-Acetyl Glucosamine (GlcNAc). It has a broad range of applications in the field of medicine, being marketed between USD 1000–5000/kg. Its primary sources include extraction of animal tissue and fermentation using pathogenic bacteria. However, in both cases, extensive purification protocols are required to prevent toxin contamination. In this study, aiming at creating a safe HA producing microorganism, the generally regarded as safe (GRAS) yeast Kluyveroymyces lactis is utilized. Initially, the hasB (UDP-Glucose dehydrogenase) gene from Xenopus laevis (xlhasB) is inserted. After that, four strains are constructed harboring different hasA (HA Synthase) genes, three of humans (hshasA1, hshasA2, and hshasA3) and one with the bacteria Pasteurella multocida (pmhasA). Transcript values analysis confirms the presence of hasA genes only in three strains. HA production is verified by scanning electron microscopy in the strain containing the pmHAS isoform. The pmHAS strain is grown in a 1.3 l bioreactor operating in a batch mode, the maximum HA levels are 1.89 g/L with a molecular weight of 2.097 MDa. This is the first study that reports HA production in K. lactis and it has the highest HA titers reported among yeast.